Classification of neck/shoulder pain in epidemiological research: a comparison of personal and occupational characteristics, disability, and prognosis among 12, 195 workers from 18 countries. Issue 5 (May 2016) - Sarquis, Leila M.M.; Coggon, David; Ntani, Georgia; Walker-Bone, Karen; Palmer, Keith T.; Felli, Vanda E.; Harari, Raul; Barrero, Lope H.; Felknor, Sarah A.; Gimeno, David; Cattrell, Anna; Vargas-Prada, Sergio; et al.
Abstract : Abstract: To inform case definition for neck/shoulder pain in epidemiological research, we compared levels of disability, patterns of association, and prognosis for pain that was limited to the neck or shoulders (LNSP) and more generalised musculoskeletal pain that involved the neck or shoulder(s) (GPNS). Baseline data on musculoskeletal pain, disability, and potential correlates were collected by questionnaire from 12, 195 workers in 47 occupational groups (mostly office workers, nurses, and manual workers) in 18 countries (response rate = 70%). Continuing pain after a mean interval of 14 months was ascertained through a follow-up questionnaire in 9150 workers from 45 occupational groups. Associations with personal and occupational factors were assessed by Poisson regression and summarised by prevalence rate ratios (PRRs). The 1-month prevalence of GPNS at baseline was much greater than that of LNSP (35.1% vs 5.6%), and it tended to be more troublesome and disabling. Unlike LNSP, the prevalence of GPNS increased with age. Moreover, it showed significantly stronger associations with somatising tendency (PRR 1.6 vs 1.3) and poor mental health (PRR 1.3 vs 1.1); greater variation between the occupational groups studied (prevalence ranging from 0% to 67.6%) that correlated poorly with the variation in LNSP; and was more persistent at follow-up (72.1% vs 61.7%). Our findings highlight important epidemiological distinctions between subcategories of neck/shoulder pain. In future epidemiological research that bases case definitions on symptoms, it would be useful to distinguish pain that is localised to the neck or shoulder from more generalised pain that happens to involve the neck/shoulder region. Abstract : Neck/shoulder pain that is associated with pain at other sites is more common and differs epidemiologically from that limited only to the neck or shoulder(s).